BULB REPLACEMENT TOOL - B.SURESH RAM, B.VENKATSWAR RAO, B.BALAKRISHNA, K.NAVYA SRI, V.SRAVANI, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Bulbs and lamps are fixed at elevated positions from the floor for proper spreading of light. One should use a ladder or some other elevated structure to reach the location where the lamps and bulbs need to be fixed. In this method there is risk of dropping down the bulb and lamp while fixing or removing and there is also possibility of a user falling or slipping down from the ladder or elevated structure therefore causing injury to him/her. To remove this problem, we are innovating the bulb replacement tool which is helpful in removing the bulb from heights without any injury to him/her. The tool will hold the bulb with the help of clamps at the top and easily remove the bulb from the holders.